Manganese(II) ions suppress the transcription of the citrate exporter encoding gene cexA in Aspergillus niger - Reinfurt, Aline; Fritsche, Susanne; Bíró, Vivien; Márton, Alexandra; Ellena, Valeria; Fekete, Erzsébet; Sándor, Erzsébet; Karaffa, Levente; Steiger, Matthias G. (Frontiers in Bioengineering and Biotechnology, 2023)
Aspergillus niger is an important filamentous fungus used for the industrial production of citric acid. One of the most important factors that affect citric acid production is the concentration of manganese(II) ions present in the culture broth. Under manganese(II)-limiting conditions, the fungus develops a pellet-like morphology that is crucial for high citric acid accumulation. The impact of manganese(II) ions on the transcription of the major citrate exporter encoding gene cexA was studied under manganese(II)-deficient and -sufficient conditions. Furthermore, citric acid production was analyzed in overexpression mutant strains of cexA in the presence and absence of manganese(II) ions, and the influence of CexA on fungal morphology was investigated by microscopy. Transcriptional upregulation of cexA in the absence of manganese(II) ions was observed and, by decoupling cexA expression from the native promoter system, it was possible to secrete more citric acid even in the presence of manganese. This effect was shown for both an inducible and a constitutive overexpression of cexA. Furthermore, it was found that the presence of CexA influences fungal morphology and promotes a higher-branched phenotype. According to this study, manganese(II) ions suppress transcription of the citrate exporter cexA in A. niger, causing citric acid secretion to decrease.